2017
DOI: 10.1249/jsr.0000000000000431
|View full text |Cite
|
Sign up to set email alerts
|

Foot Structure and Function in Habitually Barefoot and Shod Adolescents in Kenya

Abstract: Significant differences observed in foot parameters, injury prevalence and general foot health between HB and HS suggest that footwear conditions may impact on foot structure and function and general foot health. HB children and adolescents spent more time engaged in moderate to vigorous physical activity and less time sedentary than HS children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…In contrast, forefront striking, in which the ball of the foot contacts the ground before the heel, avoids the generation of impact peaks as the foot is in a more plantarflexed position upon landing and ankle compliance is increased (see Perl, Daoud, & Lieberman, ). Even on hard surfaces, shod rearfoot striking generates larger collision forces than barefoot forefront striking, potentially increasing the risk of injury (Aibast et al, ; Lieberman et al, ; Lieberman, ; Perl et al, ).…”
Section: Lower Limb Variationmentioning
confidence: 99%
“…In contrast, forefront striking, in which the ball of the foot contacts the ground before the heel, avoids the generation of impact peaks as the foot is in a more plantarflexed position upon landing and ankle compliance is increased (see Perl, Daoud, & Lieberman, ). Even on hard surfaces, shod rearfoot striking generates larger collision forces than barefoot forefront striking, potentially increasing the risk of injury (Aibast et al, ; Lieberman et al, ; Lieberman, ; Perl et al, ).…”
Section: Lower Limb Variationmentioning
confidence: 99%
“…Although Vitale et al [36] reported that performing more hours of barefoot training in martial artists, including judo athletes, confers a higher risk of lower limb injury, the correlations between barefoot activities and injuries are unclear. Studies have been contradictory regarding the relationship between foot arch height and habitual barefootedness: higher foot arches are seen in habitually barefoot than habitually shod populations of children and adolescents [1,14]. On the other hand, Cureton [7] and our recent study [30] showed that foot arch height was not associated with physical performance or TFS.…”
Section: Discussionmentioning
confidence: 76%
“…After each eligible CON was selected by matching in age and gender to JUDO volunteers, JUDO and CON were matched in body mass because muscle strength is largely affected by body size [26]. Additionally, matching groups by body mass precludes any influence of a variable load on measures of foot structure and function [1]. According to these criteria, JUDO (men, 24; age, 19.8 ± 1.3 yr; height, 168.5 ± 4.9 cm; body mass, 72.4 ± 6.4 kg; BMI, 25.5 ± 2.1 kg/m 2 ; mean ± S.D.)…”
Section: Subjectsmentioning
confidence: 99%
“…The effects of footwear on foot development have focussed primarily on the morphology of the medial longitudinal arch [ 4 , 7 , 8 , 20 , 21 ], although more recent studies are beginning to focus on the functional effects of footwear [ 4 , 19 , 22 , 23 ]. Through measurement of static footprints, Echarri and Forriol [ 7 ] investigated the development of foot morphology in 1851 Congolese children aged 3–12 years and reported that footwear had little influence on morphological parameters of the feet.…”
Section: Methodsmentioning
confidence: 99%